Pengaruh Bekam dan Olahraga terhadap Kadar Gula Darah Penderita Diabetes - B L, Abdurahman Berbudi; Ali, Mohammad; Aminoto, Toto; Lestari, Virny Dwiya (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Cupping has become an alternative treatment method that is increasingly known to the Indonesian people, marked by the proliferation of health homes or clinics that provide this service. Cupping therapy is believed to be effective in lowering blood sugar levels. Cupping is a treatment technique that uses special cups to help smooth blood flow and energy. While gymnastics is a form of physical exercise used to keep the body fit and healthy and maintain cardiopulmonary endurance. This study aims to analyze the effect of wet cupping therapy and gymnastics on reducing blood sugar levels in people with diabetes mellitus in RW 08, West Pamulang. The research design used was quasi-experimental with a pre-post test with control group approach. The sampling technique was carried out by purposive sampling, involving 40 respondents who were divided into two groups: 20 respondents as the cupping group and 20 respondents as the gymnastics group. The instruments used included the Easy Touch/Glucose Cholesterol Uric Acid (GCU) tool and observation sheets. The results showed that in the treatment group there was a significant decrease in blood sugar levels before and after wet cupping therapy, based on the Wilcoxon Signed Rank Test with a p value of 0.000 (<0.05). In the group given gymnastics training, there was also a decrease in blood sugar levels, with a paired sample t-test, a p value of 0.00 (P <0.05) was obtained. The Mann-Whitney test to compare the treatment and control groups also showed a significant difference, with a p value of 0.000 (<0.05). This decrease in blood sugar levels is influenced by various factors such as diet and frequency of therapy. Wet cupping therapy, with a duration of 30 minutes at certain points on the body, can be an alternative treatment to control blood sugar levels in people with diabetes mellitus. Researchers recommend that wet cupping therapy be carried out routinely in RW 08, West Pamulang, to maintain stable blood sugar levels so that it can reduce dependence on pharmacological therapy.